LIMITATIONS OF ARTIFICIAL INTELLIGENCE. WHY ARTIFICIAL INTELLIGENCE CANNOT REPLACE THE HUMAN MIND - Mariusz Mazurek (Filozofia i Nauka)
This paper examines the historical and contemporary challenges in the development of artificial intelligence. Replicating the human mind—with its intentionality, self-awareness, and creativity—has been, from its inception, a major challenge in artificial intelligence (AI) research. A fundamental issue remains the inability of AI systems to address “why?” and “for what purpose?” questions, underscoring the distinction between machines and humans in terms of meaning-making and contextual interpretation.